«Englishing» Dante: three recent American Poets’ Translations of the Inferno (ACME, 2022)
The essay focuses on the three main translations of Dante’s Divine Comedy done by American poets and published in the 21st century in order to compare their translating strategies, techniques, and aesthetic results. The grounds for comparison are the poet-translators’ declared intentions, the ways in which they have tried to put them into practice, and the interpretation of their results in the light of recent translation studies theory. Lawrence Venuti’s ideas about poets’ versions and about how to read a translation, especially in the context of world literature, have proven particularly useful in the case of these American poets’ attempts to rewrite a poetic text in its own right, and to carry Dante’s powerfully mastered poetic complexity across two different literary traditions.
Keywords: Dante; Inferno; translation studies; W. S. Merwin; Michael Palma; Mary Jo Bang; Lawrence Venuti; poetry translation